A Study of The Constituents of Domestic Savings and Investments in Urban Cities With Special Focus on Mumbai and Delhi - Gupta, Nupur; Agarwal, Vijay (Indian Journal of Finance, 2013)
After the economic reforms and liberalization policy of 1991, there was a shift from rudimentary finance to an organized financial system. Post independence and until liberalization, the composition of Indian household savings was primarily concentrated in physical assets as compared to financial assets. However, in the late nineties, the share of financial savings rose in various instruments - stock markets, mutual funds, market linked insurance, etc. The SEBI-NCAER study of 1999 found that around 1.4% of the population had invested in direct equity. A study done by MCX stock exchange found that 65% of the cash trading in equities happened in the cities of Mumbai and Delhi for the financial year 2009-10. The present paper examines the important constituents of domestic savings and investments by conducting a survey among 251 households in the cities of Mumbai and Delhi. The three constituents that influenced the pattern of savings and investments were the following: The city of dwelling influenced investment pattern and stock market investments. Income influenced investment pattern and stock market investments of the respondents in the age group of 40-49 years. It influenced the domestic savings of the respondents in the age group of 30-39 years. Interest rates influenced the domestic savings of households, but not their stock market investments. The present study brings out the importance of city of dwelling in making investment decisions.